Peace Literacy Education Based on Conflict Experience in Aceh - Risdam Habibi Hasibuan; Yasir Maulana Rambe; Rahmi Seri Hanida (Keraton: Journal of History Education and Culture, 2025)
This study explores the absence of Aceh’s conflict history in Indonesia’s national history curriculum and its implications for strengthening peace literacy in post-conflict education. Although values such as tolerance, diversity, and peace are emphasized in national curriculum goals, this study finds that these values are taught in isolation from local historical narratives—particularly the conflict between the Free Aceh Movement (GAM) and the Indonesian government. Using a qualitative descriptive approach and a case study method, data were collected through curriculum document analysis, history textbooks, interviews with teachers, and classroom observations in several secondary schools in Aceh. The findings reveal that history teachers face both pedagogical and institutional gaps when attempting to introduce local conflict into the classroom. The lack of teaching guidelines, learning materials, and structural support leads to generic teaching practices that avoid sensitive topics, including Aceh's conflict. As a result, students are denied access to contextual, reflective, and experience-based understandings of peace and history. This study underscores the urgency of integrating local history and peace literacy as part of reconciliatory education and calls for curriculum reform to reposition history education as a transformative, rather than merely normative, pedagogical space.